Corrupt research : the case for reconceptualizing empirical management and social science - Hubbard, Raymond T. (Sage, 2016)
Addressing the immensely important topic of research credibility, Raymond Hubbard's groundbreaking work proposes that we must treat such information with a healthy dose of skepticism. This book argues that the dominant model of knowledge procurement subscribed to in these areas - the significant difference paradigm - is philosophically suspect, methodologically impaired, and statistically broken. Hubbard introduces a more accurate, alternative framework - the significant sameness paradigm - for developing scientific knowledge. The majority of the book comprises a head-to-head comparison of the "significant difference" versus "significant sameness" conceptions of science across philosophical, methodological, and statistical perspectives--Back cover.